(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, at the end of the XIII century, in the XIV century, a class of free peasants-dedics was also preserved. Dedics were mainly dependent on the feudal lords according to the court. They were considered the heirs of the lands belonging to them. By the second half of the 14th century, the number of dedics decreased, and large secular and clerical landowners took away the dedics’ lands. In the 12th century, especially in the 13th century, Czech kings and Czech pans attracted German colonists, that is, German farmers and craftsmen, to their estates in order to increase their income.